Does CEO Characteristics Play Important Role on Malaysian Firm's Environmental Disclosure? - Mohd Waliuddin, Mohd Razali; Fathilla Ashikin, Roslanie; Brahmana, Rayenda Khresna; Sharifah Sabrina, Syed Ali (International Academy of Business and Economics, 2016)
The objective of this study is to examine the relationship between company environmental disclosures and CEO characteristics in term of tenure and education background such as MBA (Master in Business Administration) and legal background. Sample data collected from annual reports of companies listed in Bursa Malaysia in financial year end as 31st December consist 74 companies listed in Malaysia with various sector and in years from 2011 till 2013. The result shows that CEO’s tenure and CEO with legal education have negative relationship with the environmental disclosure. Only one of controlling variables which is size has positive relationship with environmental disclosure. The study concludes that CEO who has work long in the company tents and CEO with legal background may have less willingness to take risk to disclosure environmental information.